2019
DOI: 10.3390/en12050847
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Analysis of Homogeneous Charge Compression Ignition in a Motorcycle Engine Using a Dual-Fuel with Exhaust Gas Recirculation

Abstract: Exhaust emissions from the large population of motorcycles are a major issue in Asian countries. The regulation of exhaust emissions is therefore becoming increasingly stringent, with those relating to nitrogen oxides (NOx) the most difficult to pass. The homogeneous charge compression ignition (HCCI) has special combustion characteristics and hence produces low NOx emissions and exhibits high thermal efficiency. This study developed an HCCI system for a 150 cc motorcycle engine. The target engine was modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In general, higher ethanol percentages or other alternative fuels result in lower emissions [33][34][35][36][37][38][39][40][41]. Even further reductions are expected with other combustion concepts [42] or hybridization [43]. Thus the emissions of future mopeds and motorcycles should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…In general, higher ethanol percentages or other alternative fuels result in lower emissions [33][34][35][36][37][38][39][40][41]. Even further reductions are expected with other combustion concepts [42] or hybridization [43]. Thus the emissions of future mopeds and motorcycles should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Bahram B et al found the in-cylinder pressure at 5, 10, 15 and 20 °C. A top dead center was the key factor determining engine misfires [7].…”
Section: Hcci Engine Misfire Detectionmentioning
confidence: 99%
“…On the other hand, the literatures [6,7] deal with analyzing specific combustion characteristics occurred in an engine under load. In line with these aspects, the authors in [6] evaluate capabilities of low-temperature combustion concept to operation of a medium-duty compression ignition engine (hereinafter referred to as CI) proposing multiple approaches to solve its crucial challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with these aspects, the authors in [6] evaluate capabilities of low-temperature combustion concept to operation of a medium-duty compression ignition engine (hereinafter referred to as CI) proposing multiple approaches to solve its crucial challenges. Wu and Jang also carried out engine combustion analysis, in which they designed a modified homogeneous charge compression ignition system for a 150cc motorcycle engine [7].…”
Section: Literature Reviewmentioning
confidence: 99%